Terapia comportamental e cognitiva para insônia focada na preocupação (TCC-Ip), em duas fases, utilizando as técnicas de distração de atenção e imagem mental - Molen, Yara Fleury Van der [UNIFESP] (2018)
Objective: Evaluate the effect of a cognitive behavior therapy treatment for insomnia focusing in worries (wCBT-I), consisting of two phases and utilizing distraction of attention and imagery as tools for dealing with worries. Methods: In this prospective study, after obtaining 2 weeks of baseline data, thirty one participants received a wCBT-I treatment. The first phase comprised 3 weeks of a 2 hour-weekly meeting, with educational speeches about worry as an insomnia maintaining factor, sleep hygiene, dysfunctional beliefs and attitudes about sleep, microanalytic and cognitive models of insomnia, cognitive restructuring and a practice of distraction of attention by reading. Participants were instructed to read for 15 minutes before bedtime. Phase 2, with 3 week of a 2-hour weekly meeting had the same participants receiving speeches and practice on imagery rehearsal, with instructions to follow every night 15 minutes of an audio CD before bedtime with relaxation and imagery. The imagery practice instructed the participants to get rid of emotions related with worries which prevented them from sleeping. Sleep diaries provided sleep onset latency (SL), wake after sleep onset (WASO), early morning awakening (EMA), total sleep time (TST), sleep efficiency (SE) and number of awakenings (NA). Questionnaires provided data for insomnia severity, general worry, sleepspecific worry, sleep disturbance, dysfunctional beliefs and attitudes about sleep, and anxiety. Follow-up measures were obtained 4 weeks after the end of phase-1 and phase-2. Results: Although SL, WASO, EMA, TST, SE and NA have shown improvement in phase-1, the results were not significant compared to baseline. In phase-2, TST and SE showed a significant increase compared to baseline. In relation to phase-1 post-treatment (PT-1), TST and SE enhanced significantly in phase-2 post-treatment (PT-2). The decrease in sleep onset latency (SL) was not significant, but represented a clinically relevant improvement at follow-up in phase 2 (FU-2), considering that its value in FU-2 was lower than the clinical cut off of 30 minutes. The scale scores of ISI, PSWQ, DBAS-10, SDQ, SSTAI, sleep-specific worry and depression were significantly reduced after intervention. Worry score lower than 50, considered as a cut-off point for discriminating non-anxious populations was found in 65% of the participants. The changes occurring in the ability to calm the mind was learned during the intervention, either by transforming beliefs and attitudes about sleep, by utilizing cognitive restructuring, by relaxing, using distraction of attention or imagery training. Conclusions: The wCBT-I treatment contributed to a significant increase in total sleep time and sleep efficiency and a clinical improvement in sleep onset latency. The Insomnia severity, general worry and sleep specific worry, dysfunction beliefs and atitudes about sleep, sleep disturbance, state anxiety and depression were significantly reduced after intervention. Distraction of attention as well as imagery should be considered options to be included in tailored treatment for insomnia as abilities for coping with worries in general and sleep related worries, as strategies to deal with emotions in insomnia therapeutics and also as a useful way to break the insomnia perpetuation cycle and reduce comorbid depression. Adding to the educational component the theoretical models of insomnia which explain the role of worry in insomnia, increasing the awareness about worry as an insomnia maintaining factor, and introducing the practice of distraction of attention by reading and imagery before bedtime may be beneficial to diminish the distress experienced by the insomniac related to the sleeping difficult.